Method for the regeneration of platinum-rhenium spent catalyst to produce a modified platinum-based catalyst for fuel cells, catalyst and hydrogen energy fuel cell
Patent Information
- Application Number
- CN202310686724.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-06-09
AI Technical Summary
但该过程会产生大量的废水,部分溶解的载体分离困难,回收贵金属产品未进一步实现高值化利用
[0069] 1) The method for regenerating platinum-containing rhenium waste catalyst to prepare platinum-based catalysts for fuel cells provided by the present invention is simple to operate, has a short process, and the prepared catalyst has high stability and good electrochemical performance;
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and more specifically to a method for recovering and regenerating metals from platinum- and rhenium-containing waste catalysts to prepare modified platinum-based catalysts for fuel cells. Background Technology
[0002] Catalytic reforming is an important means of improving gasoline quality and producing petrochemical feedstocks. The main metal component of catalytic reforming catalysts is platinum, with alumina as the support. With the needs of industrial development, platinum-rhenium bimetallic catalysts have become popular in catalytic reforming, increasing the depth of the reforming reaction and the yield of gasoline, aromatics, and hydrogen, thus bringing catalytic reforming technology to a new level.
[0003] A fuel cell is a chemical device that directly converts the chemical energy of fuel into electrical energy, and the hydrogen energy industry has broad development prospects. Among them, hydrogen fuel cells have become an ideal power battery for electric vehicles due to their advantages such as no pollution, no noise, and high efficiency. The catalyst is a crucial component of hydrogen fuel cells, primarily a Pt / C catalyst, accounting for 36% of the fuel cell stack cost. Platinum has stable physicochemical properties and good catalytic performance, and is widely used in the catalysis field; however, platinum is expensive, and my country's reserves are extremely low, making it mainly dependent on imports. The rare and precious metals in platinum-rhenium waste catalysts have a higher grade than those in ores. After recovery, they can be used as active metals in fuel cell catalysts and applied in hydrogen fuel cells. This can reduce production costs, increase platinum resource supply, reduce dependence on imports, and realize the value-added utilization of hazardous waste, making it extremely valuable.
[0004] Chinese patent CN101380597B discloses a method for removing oily substances from petrochemical waste catalysts. The method proposes adding 0.5–1.0% by weight of a water-soluble polymeric dispersant to the oil-containing waste catalyst, under a pressure of 1.5–6.0 × 10⁻⁶. 4 Oil is removed by distillation at 300–600℃. This method involves the interaction of an aqueous solution of a polymeric dispersant with the oil in spent petrochemical catalysts under high temperature and pressure, leading to desorption from the catalyst surface.
[0005] Chinese patent CN114522699A discloses a method for removing oil from the surface of waste oil refining catalysts. The method involves mixing the ground waste oil refining catalyst with a 5-15 wt% hydrogen peroxide solution or a 50-100 mmol / L persulfate solution, followed by solid-liquid separation to obtain the de-oiled catalyst. This method utilizes the Fenton effect of hydrogen peroxide and persulfate to oxidize and decompose oily substances, thereby removing the oil adhering to the waste catalyst. However, the introduction of strong oxidants generates wastewater during the oil removal process, posing certain environmental hazards.
[0006] Chinese patent CN107190147A discloses a method for removing carbon deposits and organic matter from platinum-containing waste catalysts through oxidative roasting, followed by platinum leaching using inorganic acids, and then enrichment and purification of the platinum through adsorption using an R410 resin column, ultimately yielding a sponge platinum product through reduction. This method, as a typical wet recycling process, removes oil and recovers precious metals from the waste catalyst with a high recovery rate. However, the roasting process generates harmful exhaust gases, and the acid leaching process uses large amounts of acid and produces significant amounts of wastewater.
[0007] Chinese patent CN108913919B discloses a method for extracting rhenium from spent platinum-rhenium catalysts. This method involves high-pressure acid leaching of platinum-rhenium-containing spent catalysts and anion exchange resin processes to obtain ammonium rheniumate, etc. This method achieves a high rhenium recovery rate and produces high-purity recovered products. However, this method does not treat the support and the active platinum metal, and the recovered metal is not utilized for high-value purposes.
[0008] Chinese patent CN109126777A discloses a method for preparing Pt / C catalysts from platinum-containing waste catalysts, which also belongs to the field of precious metal recycling technology. The method involves calcining, oxidizing, and filtering the platinum-containing waste catalyst to obtain a crude chloroplatinic acid solution, followed by extraction and back-extraction to obtain a sodium chloroplatinate solution. Finally, this solution is mixed with a carbon black support for reduction, filtered, and dried to obtain the Pt / C catalyst. The Pt / C catalyst prepared by this method has a low active metal loading and does not achieve complete recovery of the metal components, including the support.
[0009] The inventions in the above patents concerning the pretreatment process for oil removal from spent catalysts achieve oil removal through the interaction between the oil adhering to the petrochemical spent catalyst and the oil removal agent, avoiding problems such as thermal runaway and waste gas generation caused by direct roasting for oil removal. However, the experimental conditions for the oil removal process are quite harsh, and it is also prone to generating a large amount of wastewater. The inventions in the above patents concerning the recovery of rare and precious metals from spent catalysts mainly achieve the recovery of platinum group metals through processes such as acid leaching and ion exchange. The oxidative acid leaching process has a high leaching rate, and ion exchange can selectively adsorb and separate precious metal components; this process is also known as a commonly used wet recovery method in industry. However, this process generates a large amount of wastewater, the separation of partially dissolved carriers is difficult, and the recovered precious metal products are not further utilized for high-value purposes. Summary of the Invention
[0010] The purpose of this invention is to provide a method for regenerating platinum-rhenium spent catalysts to prepare modified platinum-based catalysts for fuel cells, the catalyst itself, and a hydrogen fuel cell. This method enables oil removal and pretreatment of spent catalysts, recovery of valuable metals, and the preparation of regenerated catalysts for application in fuel cells, achieving the harmless, reduced-volume, and resource-based treatment of hazardous waste. This invention has the advantages of simple process, low cost, and environmental friendliness. The regenerated catalyst exhibits stable performance and high catalytic activity.
[0011] The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts provided by the present invention includes the following steps:
[0012] (1) Remove oil adhering to platinum-rhenium waste catalyst with alumina as support;
[0013] (2) The waste catalyst treated in step (1) and sodium hydroxide powder are mixed and then heat-treated in an oxygen-free environment to obtain clinker;
[0014] (3) The clinker is leached in a weakly alkaline aqueous solution to obtain a first leachate containing Al and most of Re and a first leach residue containing Pt and a small amount of Re;
[0015] (4) The first leachate is converted into sodium aluminate solution and sodium perrhenate solution;
[0016] (5) Add an aqueous solution of an acidic reagent and an aqueous solution of an oxidizing reagent to the first leaching residue for oxidative acid leaching to obtain a second leaching solution containing precursors of platinum and rhenium.
[0017] (6) The precursor containing platinum and rhenium in the second leachate is reduced and loaded onto a carbon support to obtain a rhenium-doped Pt / C catalyst, thereby obtaining the modified platinum-based catalyst for fuel cells.
[0018] In the above-mentioned method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, the mass percentage of alumina in the platinum-rhenium waste catalyst is 95-97%, such as 95%, 95.8%, or 97%.
[0019] The platinum-containing rhenium waste catalyst has a platinum content of 0.2% to 0.3% by mass, such as 0.22%, 0.24%, or 0.25%.
[0020] The mass percentage of rhenium, the active metal component, in the platinum-rhenium-containing waste catalyst is 0.4-0.5%, such as 0.43% or 0.45%.
[0021] In step (1), the oil removal process is as follows: the platinum-rhenium-containing waste catalyst is ground into powder, a compound surfactant solution is added and the catalyst is cleaned under ultrasonic conditions to obtain the de-oiled waste catalyst;
[0022] The powdered platinum-rhenium spent catalyst has a particle size of 100-200 mesh, specifically 100 mesh, and is prepared by ball milling at 500 r / min for 5 h in a specific embodiment of the present invention;
[0023] The compound surfactant is composed of a nonionic surfactant and anionic surfactant.
[0024] The nonionic surfactant is selected from any one of fatty alcohol polyoxyethylene ether (AEO-3), Triton X-100 (TX-100), and glucoside (APG1214);
[0025] The anionic surfactant is selected from any one of sodium dodecylbenzene sulfonate (SDBS), sodium fatty alcohol polyoxyethylene ether sulfate (AES), and sodium dodecyl sulfonate (SLS);
[0026] The mass ratio of the nonionic surfactant to the anionic surfactant is (1-4):1, such as 1:1, 2:1, 3:1 or 4:1;
[0027] The concentration of the aqueous solution of the compound surfactant is 100-1000 mg / L, specifically 100-900 mg / L, such as 100 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, 800 mg / L or 900 mg / L;
[0028] The mass ratio of the platinum-rhenium-containing waste catalyst to the volume ratio of the aqueous solution of the surfactant is 1g:(10-100)mL, preferably 1g:(10-60)mL, and specifically can be 1g:10mL, 1g:20mL, 1g:30mL, 1g:40mL, 1g:50mL or 1g:60mL.
[0029] The ultrasonic power is 100-500W (e.g., 200-500W, 200W, 300W or 500W), the cleaning temperature is 25-60℃ (e.g., 40-50℃, 40℃ or 50℃), and the cleaning time is 1-4h (e.g., 1h, 2h or 4h).
[0030] Preferably, the specific conditions are as follows: the compound surfactant is composed of SDBS and APG solutions with a mass ratio of 1:2 and a concentration of 800 mg / L; the mass ratio of the platinum-rhenium-containing waste catalyst to the volume ratio of the aqueous solution of the surfactant is 1 g: 60 mL; the ultrasonic power is 200 W; and the cleaning time is 1 h.
[0031] In this invention, the working principle of the pretreatment in step (1) is as follows: the oily waste catalyst is cleaned by the surfactant solution in an ultrasonic environment. The surfactant can significantly reduce the interfacial tension between oil and water, so that the oil droplets are dispersed into small droplets and dissolved in the surfactant micelles. The cavitation effect of ultrasound can increase the fluidity of the oil, and further realize the removal of oil from the waste catalyst.
[0032] In the above-mentioned method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, in step (2), the mass ratio of the waste catalyst treated in step (1) to the sodium hydroxide powder is 1:(0.8-1.6), specifically 1:(1-1.4), 1:1.2, 1:1.4 or 1:1;
[0033] The oxygen-free environment is under the protection of an inert gas, such as nitrogen and / or argon;
[0034] The heat treatment temperature is 300-600℃, specifically 300℃, 500℃, 600℃ or 400℃, and the time is 1-5h, specifically 2h, 1h, 3h or 5h.
[0035] In this invention, the working principle of step (2) anaerobic sodium annealing heat treatment is as follows: The support in the waste catalyst is alumina, which can react with sodium hydroxide at high temperature to generate sodium aluminate as a byproduct. Active metal rhenium exists in the form of elemental form and oxides. Under aerobic conditions, rhenium reacts to generate rhenium heptaoxide, a volatile substance that causes mass loss. During sodium annealing heat treatment, rhenium and its oxides react to generate sodium perrhenate as a byproduct. Active metal Pt does not react.
[0036] In the above-mentioned method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, in step (3), the pH value of the weakly alkaline aqueous solution is 7.1 to 8.9, such as 8 to 8.5, 8.5, 8.0 or 7.5;
[0037] The solute in the weakly alkaline aqueous solution is sodium hydroxide, sodium carbonate, or sodium bicarbonate.
[0038] The mass ratio of the clinker to the volume ratio of the weakly alkaline aqueous solution is 1g:(10-20)mL, specifically 1g:10mL;
[0039] The leaching is carried out under stirring conditions, with a leaching temperature of 25–60°C (e.g., 40–50°C, 40°C, 50°C) and a leaching time of 10–60 min (e.g., 20–40 min, 30 min, 40 min, or 20 min).
[0040] In this invention, the working principle of the weakly alkaline leaching in step (3) is as follows: the clinker obtained in step (2) is leached, and the main components of the roasted clinker are sodium aluminate and a small amount of sodium perrhenate. Sodium aluminate and sodium perrhenate enter the liquid phase, while platinum acts as the slag phase. The weakly alkaline environment can inhibit the hydrolysis of sodium aluminate and increase the yield of sodium aluminate as a byproduct.
[0041] In the above-mentioned method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, step (4) involves converting the first leachate into sodium aluminate solution and sodium perrhenate solution as follows: The first leachate is passed through an exchange column containing an imprinted resin capable of selectively adsorbing rhenium anion groups, and the exchange tail liquid is collected. The sodium aluminate solution is obtained. After adsorption is complete, the desorbed liquid is passed through the resin for desorption to obtain the sodium perrhenate solution.
[0042] Preferably, the imprinting resin is an ion-imprinted imprinting resin containing polystyrene groups;
[0043] Preferably, the volume ratio of the first leachate to the imprinting resin is (5-10):1 (e.g., 10:1, 6:1 or 8:1), the adsorption temperature is 25-50℃ (e.g., 40-50℃, 50℃, 40℃), and the adsorption time is 10-30min (e.g., 0.5h, 20min or 10min).
[0044] Preferably, the desorption solution is a sodium hydroxide solution with a concentration of 1-2 mol / L (e.g., 1.5 mol / L, 1 mol / L), the volume ratio of the desorption solution to the imprinting resin is (5-10):1 (e.g., 5:1, 6:1 or 8:1), the desorption temperature is 25-50℃ (e.g., 40-50℃, 50℃, 40℃), and the desorption time is 30-120 min (e.g., 30-50 min, 50 min, 30 min).
[0045] In this invention, the working principle of step (4) is as follows: the first leachate is selectively adsorbed and separated by the imprinting resin, and the functional groups on the resin selectively adsorb ReO4. - The exchanged tail liquid is a sodium aluminate solution, and the resin is desorbed to obtain a sodium perrhenate solution. The desorbed resin can be recycled.
[0046] In the above-mentioned method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, in step (5), the acidic reagent is hydrochloric acid;
[0047] The concentration of the aqueous solution of the acidic reagent is 0.1–0.5 mol / L, specifically 0.2 mol / L, 0.1 mol / L, 0.3 mol / L, or 0.5 mol / L;
[0048] The mass ratio of the first leaching residue to the volume ratio of the aqueous solution of the acidic reagent is 1g:(1~5)mL, such as 1g:1mL or 1g:2mL;
[0049] The oxidizing agent is hydrogen peroxide;
[0050] The volume concentration of the aqueous solution of the oxidizing agent is 10-30%, specifically 10%-20%, 20%, 10%, 15%, or 18%.
[0051] The mass ratio of the first leaching residue to the volume ratio of the aqueous solution of the oxidizing agent is 1g:(0.5~1)mL, such as 1g:0.5mL, 1g:1mL or 1g:0.8mL;
[0052] The oxidative acid leaching temperature is 25–50°C (e.g., 50°C), and the time is 0.5–2 hours (e.g., 1 hour, 0.5 hours).
[0053] The precursors containing platinum and rhenium are chloroplatinic acid and perrhenic acid.
[0054] In this invention, the working principle of step (5) is as follows: the first leaching residue is subjected to oxidative acid leaching (HCl+H2O2) to generate a mixed solution of chloroplatinic acid and perrhenic acid, which can be used as a precursor solution for preparing modified platinum-based catalysts.
[0055] In the above-mentioned method for regenerating platinum and rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, in step (6), the step of reducing the precursor containing platinum and rhenium elements in the second leachate and loading it onto a carbon support is as follows: the carbon support is dispersed in an alkaline ethylene glycol solution, the second leachate is added, a reduction reaction is carried out under microwave assistance, and the reaction product is acidified, washed and dried in sequence to obtain the modified platinum-based catalyst for fuel cells;
[0056] The carbon support is carbon black, graphene, or carbon nanotubes.
[0057] The alkaline ethylene glycol solution has a pH of 11-12 (e.g., 11 or 12), and the alkaline reagent is a sodium hydroxide solution.
[0058] The volume ratio of the alkaline ethylene glycol solution to the second leachate is (2-11):25, such as (5-8):25, 5:25 or 8:25;
[0059] The microwave power is 800-1200W (e.g., 800W, 900W, 1000W, 1100W or 1200W), and it is carried out under normal pressure conditions;
[0060] The reduction reaction is carried out at a temperature of 140–190°C (e.g., 170–190°C, 170°C, 180°C, or 190°C) for a time of 2–3 min (e.g., 2 min or 3 min).
[0061] In the acidification step, the pH value is adjusted to 2-3 (e.g., pH=2);
[0062] The acidification step uses dilute hydrochloric acid, dilute sulfuric acid, or dilute nitric acid.
[0063] The stabilization time in the acidification step is 12 to 36 hours, such as 12 hours, 18 hours, or 36 hours.
[0064] In this invention, step (6) is the synthesis process of the modified Pt / C catalyst, and its working principle is as follows: First, the carbon support is dispersed in an alkaline ethylene glycol solution, and a leaching solution containing rare and precious metals is added. Ethylene glycol can decompose into intermediate substances with certain reducing properties, such as glyoxal, at high temperatures. These substances can reduce common precious metal (such as Pt) precursors to elemental metals. In addition, glyoxal is converted into oxalate anions as the reaction proceeds and adsorbed on the metal surface. Under weakly alkaline conditions, the metal particles repel each other, thereby preventing the growth of metal particles and obtaining nanoparticles with smaller particle sizes. The reaction product obtained in step (6) is acidified with dilute sulfuric acid and stabilized at pH 2, which can break the colloidal environment generated by the alkaline medium coordination in the previous step. Then, it is washed and dried to synthesize the modified platinum-based catalyst for fuel cells.
[0065] In the above-mentioned method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalyst for fuel cells, the loading of Pt in the modified platinum-based catalyst for fuel cells is 5-30% (e.g., 19%, 17%, 20%, 21%, 18%, 22.3%), and the loading of Re is 0.5-1.5% (e.g., 0.5%, 0.93%, 1.12%, 1.02%, 0.89%, 1.35%, 0.97%).
[0066] The present invention further provides a modified platinum-based catalyst for fuel cells prepared by any of the above-described preparation methods.
[0067] A hydrogen fuel cell comprising the modified platinum-based catalyst described above is also within the scope of this invention.
[0068] This invention provides a method for regenerating and preparing modified platinum-based catalysts for fuel cells from platinum-rhenium-containing waste catalysts, which has the following advantages:
[0069] 1) The method for regenerating platinum-containing rhenium waste catalyst to prepare platinum-based catalysts for fuel cells provided by the present invention is simple to operate, has a short process, and the prepared catalyst has high stability and good electrochemical performance;
[0070] 2) The method for regenerating platinum-containing rhenium waste catalysts to prepare platinum-based catalysts for fuel cells provided by the present invention can realize the recovery of Re and Al components in waste catalysts, the recovery product has high purity, and the Pt in waste catalysts can be utilized at high value.
[0071] 3) The byproducts of the method for regenerating platinum-containing rhenium waste catalysts to prepare platinum-based catalysts for fuel cells provided by the present invention are sodium aluminate and sodium perrhenate. The sodium aluminate byproduct can be used as a precursor for the preparation of aluminum-based petrochemical catalyst supports. A mesoporous alumina support with a high specific surface area can be prepared by precipitation, thereby realizing the regeneration and utilization of the support. The sodium perrhenate solution byproduct can be used as an active component in the regenerated catalyst. The active metal can be loaded onto the catalyst support by impregnation and reduction, thereby realizing the regeneration and utilization of sodium perrhenate. Attached Figure Description
[0072] Figure 1 This is a process flow diagram of the method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts in an embodiment of the present invention.
[0073] Figure 2 XRD characterization of the heat-treated clinker in step (3) of Embodiment 1 of the present invention.
[0074] Figure 3 XRD characterization of the modified platinum-based catalyst synthesized in step (8) of Example 1 of this invention.
[0075] Figure 4 Electrochemical performance testing of the modified platinum-based catalyst synthesized in step (8) of Example 1 of this invention. Detailed Implementation
[0076] To better understand the objectives, technical solutions, and advantages of this invention, a method for regenerating platinum-rhenium waste catalyst to prepare modified platinum-based catalysts for fuel cells according to this invention is described in further detail below with reference to the accompanying drawings and embodiments. However, the scope of protection of this invention is not limited to the following description. The given embodiments are only for illustrating this invention and are not intended to limit the scope of this invention. The embodiments provided below can serve as a guide for those skilled in the art to make further improvements and do not constitute a limitation on this invention in any way.
[0077] The calculation formulas in the following examples are as follows:
[0078] (1) Oil removal rate
[0079]
[0080] In the formula, α is the removal rate of waste catalyst oil, %; C0 is the initial oil content of the waste catalyst, g / 100g; C i The oil content of the catalyst after degreasing is expressed in g / 100g. The initial oil content and the oil content after degreasing of the spent catalyst were determined by solid-liquid extraction using a Soxhlet extractor (extractant: C2Cl4), and quantitatively analyzed using an infrared spectrophotometer.
[0081] (2) Leaching rate
[0082]
[0083] In the formula x i ρ represents the leaching rate of the element, %; n represents the sample dilution factor; V represents the volume of the leachate, mL; C represents the leaching concentration. i The concentrations of each element in the ICP test are in mg / L; m is the mass of the added raw material sample in g; w i The percentage of each element in the raw material is expressed as %.
[0084] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; and the materials and reagents used are commercially available unless otherwise specified.
[0085] Example 1: Preparation of modified platinum-based catalyst for fuel cells by regeneration of platinum-rhenium spent catalyst.
[0086] according to Figure 1 The flowchart shown is prepared using the following specific steps:
[0087] (1) Take 10g of platinum-rhenium waste catalyst (based on catalyst mass, alumina accounts for 95wt%, active metal component platinum accounts for 0.22wt%, active metal rhenium accounts for 0.43wt%) and ball mill it in a ball mill. Set the speed to 500r / min and the ball milling time to 5h. After ball milling, pass the sample through a 100-mesh sieve for later use.
[0088] (2) The sample from step (1) was added to 100 mL of a cleaning solution containing surfactants SDBS and AEO-3. The mass ratio of SDBS to AEO-3 solution was 1:1 and the concentration was 100 mg / L. The solution was placed in a 40°C water bath constant temperature shaker for 1 hour and 200 W ultrasonic waves (intermittent) were applied to it to ultrasonically clean and remove oil from the waste catalyst powder, resulting in de-oiled waste catalyst powder. In this embodiment, the de-oiling rate of the waste catalyst was 91.53%.
[0089] (3) The spent catalyst powder obtained in step (2) was dried and weighed, with a mass of 9.13 g. 10.96 g of sodium hydroxide granules were weighed according to a mass ratio of spent catalyst to sodium hydroxide of 1:1.2 and ground in a mortar until fully mixed. The mixture was then transferred to a corundum crucible, placed in a tube furnace, and protected with argon gas to create an oxygen-free environment. After continuous and uniform purging for 30 min, the sample was heat-treated at 500℃ for 2 h. After the reaction, 17.72 g of clinker was obtained. The main component of the clinker was sodium aluminate. Clinker characterization is shown in [link to clinker characterization]. Figure 2 .
[0090] (4) Take the clinker obtained in step (3) and put it into a 250mL beaker. Add 180mL of weakly alkaline aqueous solution. The weakly alkaline solution is prepared with sodium hydroxide and the pH of the solution is 8.5. Stir magnetically in a 40℃ water bath for 30min. After leaching, centrifuge the sample at high speed. Set the centrifuge speed to 10000rpm / min and the centrifugation time to 10min to obtain a leachate containing Al and Re and a leachate residue containing Pt and a small amount of Re. Dilute the leachate 10 times and 1000 times respectively, and detect the leaching rate of element Re and element Al in the leachate by ICP-OES. The test results show that the leaching rate of Re is 93.52% and the leaching rate of Al is 98.12%.
[0091] (5) Pass the leachate from step (4) into an exchange column containing imprinted resin. The resin is polystyrene imprinted resin, manufactured by Boer Chemical Reagents, model: crosslinked 1% DVB (100-200 mesh). The volume ratio of resin to leachate is 1:10, the adsorption temperature is 50℃, the adsorption time is 30min, and the tail liquid of the exchange is sodium aluminate solution. After the adsorption is completed, 90mL of 1.5mol / L sodium hydroxide solution is passed into the resin for desorption according to the volume ratio of desorption solution to resin of 5:1. The desorption time is 50min, and the desorption temperature is the same as the adsorption temperature to obtain sodium perrhenate solution.
[0092] (6) Add 1 mL of 0.1 mol / L hydrochloric acid solution and 0.5 mL of 10 vol% H2O2 solution to the leaching residue obtained in step (4). In this embodiment, the solid-liquid ratio of leaching residue and hydrochloric acid solution is 1:1 g / mL, and the ratio of leaching residue and hydrogen peroxide solution is 1:0.5 g / mL. The reaction time is 1 h and the reaction temperature is 50 °C, and a leachate containing chloroplatinic acid and perrhenic acid is obtained.
[0093] (7) Disperse carbon black in an alkaline ethylene glycol solution, the alkaline solution being sodium hydroxide solution with a pH of 12, and add the leachate obtained in step (6). In this example, the amount of carbon black used is 80 mg, the amount of alkaline ethylene glycol solution is 5 mL, and the volume of leachate is 25 mL. React under microwave assistance, with a microwave power of 900 W, a reaction temperature of 170 °C, and a reaction time of 2 min.
[0094] (8) The reaction product obtained in step (7) was adjusted to pH 2 by adding 0.5 mol / L H2SO4 solution and stabilized for 12 h. After washing and drying, the regenerated modified platinum-based catalyst for fuel cell preparation was obtained. The XRD characterization of the catalyst is shown in [reference needed]. Figure 3 .
[0095] The loading of active metals Pt and Re and the electrochemical performance test results of the regenerated catalyst prepared in this embodiment are shown in Table 1. After sample dissolution, ICP-OES analysis showed that the Pt loading reached 19 wt% and the Re loading reached 0.5 wt%, indicating that the recovered rare and precious metals were well loaded on the active sites of the carbon black support. The modified catalyst prepared by regeneration was then subjected to electrochemical performance testing. The electrochemical performance tests in this embodiment were performed on a rotating disk electrode and an electrochemical workstation. The working electrode was a glassy carbon electrode, the reference electrode was a Hg / HgSO4 electrode, and the counter electrode was graphite. The electrolyte solution was 0.1 M perchloric acid (under oxygen saturation conditions), and the test method was linear sweep voltammetry, performed at room temperature and pressure. The half-wave potential of the catalyst prepared in this embodiment was 0.86 V, which is better than that of the commercial Pt / C catalyst (the commercial Pt / C catalyst with a platinum loading of 20 wt% has a corresponding half-wave potential of 0.83 V). The half-wave potential test process is described in [link to test procedure]. Figure 4 .
[0096] Example 2: Preparation of modified platinum-based catalyst for fuel cells by regeneration of platinum-rhenium spent catalyst.
[0097] according to Figure 1 The flowchart shown is prepared using the following specific steps:
[0098] (1) Take 10g of waste catalyst (based on catalyst mass, alumina accounts for 95.8wt%, active metal component platinum accounts for 0.24wt%, active metal rhenium accounts for 0.45wt%) and ball mill it in a ball mill. Set the speed to 500r / min and the ball milling time to 5h. After ball milling, pass the sample through a 100-mesh sieve for later use.
[0099] (2) The sample from step (1) was added to 200 mL of a cleaning solution containing surfactants SLS and TX-100. The mass ratio of SLS to TX-100 solution was 1:3 and the concentration was 400 mg / L. The solution was placed in a 50°C water bath constant temperature shaker for 2 hours. 300 W ultrasonic waves (intermittent) were applied to the solution to ultrasonically clean and remove oil from the waste catalyst powder, resulting in de-oiled waste catalyst powder. In this embodiment, the de-oiling rate of the waste catalyst was 95.32%.
[0100] (3) The spent catalyst powder obtained in step (2) was dried and weighed, with a mass of 9.06 g. 12.68 g of sodium hydroxide granules were weighed according to a mass ratio of spent catalyst to sodium hydroxide of 1:1.4 and ground in a mortar until fully mixed. The mixture was then transferred to a corundum crucible, placed in a tube furnace, and protected with argon gas to create an oxygen-free environment. After continuous and uniform gas flow for 30 min, the sample was heat-treated at 600℃ for 1 h. 18.55 g of clinker was obtained after the reaction.
[0101] (4) Take the clinker obtained in step (3) and put it into a 250mL beaker. Add 190mL of weakly alkaline aqueous solution. The weakly alkaline solution is prepared with sodium carbonate and the pH of the solution is 8.0. Stir magnetically in a 40℃ water bath for 40min. After leaching, the sample is separated by high-speed centrifugation. The centrifuge speed is set to 10000rpm / min and the centrifugation time is 10min to obtain a leachate containing Al and Re and a leachate residue containing Pt and a small amount of Re. The leachate is diluted 10 times and 1000 times respectively, and the leaching rate of element Re and element Al in the leachate is detected by ICP-OES. The test results show that the leaching rate of Re is 96.20% and the leaching rate of Al is 99.82%.
[0102] (5) Pass the leachate from step (4) into an exchange column containing imprinted resin. The resin is polystyrene-based imprinted resin. The purchaser and model are the same as in Example 1. The volume ratio of resin to leachate is 1:6. The adsorption temperature is 40℃. The adsorption time is 20min. The tail liquid of the exchange is sodium aluminate solution. After the adsorption is completed, 158mL of 1mol / L sodium hydroxide solution is passed into the resin for desorption according to the volume ratio of desorption liquid to resin is 5:1. The desorption time is 30min. The desorption temperature is the same as the adsorption temperature to obtain sodium perrhenate solution.
[0103] (6) Add 1 mL of 0.3 mol / L hydrochloric acid solution and 1 mL of 15 vol% H2O2 solution to the leaching residue obtained in step (4). In this embodiment, the solid-liquid ratio of leaching residue and hydrochloric acid solution is 1:1 g / mL, and the ratio of leaching residue and hydrogen peroxide solution is 1:1 g / mL. The reaction time is 1 h and the reaction temperature is 50 °C, and a leachate containing chloroplatinic acid and perrhenic acid is obtained.
[0104] (7) Disperse carbon black in an alkaline ethylene glycol solution, the alkaline solution being sodium hydroxide solution with a pH of 12, and add the leachate obtained in step (6). In this example, the amount of carbon black used is 80 mg, the amount of alkaline ethylene glycol solution is 5 mL, and the volume of leachate is 25 mL. React under microwave assistance, with a microwave power of 1000 W, a reaction temperature of 180 °C, and a reaction time of 2 min.
[0105] (8) Add 0.5 mol / L HNO3 solution to the reaction product obtained in step (7) to adjust the pH to 2 and stabilize it for 18 h. After washing and drying, the modified platinum-based catalyst for regeneration and preparation of fuel cells is obtained.
[0106] The loading of active metals Pt and Re and the electrochemical performance test results of the regenerated catalyst prepared in this embodiment are shown in Table 1. After sample dissolution, ICP-OES analysis showed that the Pt loading reached 16 wt% and the Re loading reached 0.43 wt%, indicating a decrease in the loading of rare and precious metals on the carbon black support after recovery. The modified catalyst prepared by regeneration was subjected to electrochemical performance testing (test system and conditions were the same as in Example 1). The half-wave potential of the catalyst prepared in this embodiment was 0.82 V, which is slightly worse than that of the commercial Pt / C catalyst (the platinum loading and corresponding half-wave potential of the commercial Pt / C catalyst are the same as in Example 1).
[0107] Example 3: Preparation of modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts.
[0108] according to Figure 1 The flowchart shown is prepared using the following specific steps:
[0109] (1) Take 10g of waste catalyst (based on catalyst mass, alumina accounts for 97wt%, active metal component platinum accounts for 0.25wt%, active metal rhenium accounts for 0.43wt%) and ball mill it in a ball mill. Set the speed to 500r / min and the ball milling time to 5h. After ball milling, pass the sample through a 100-mesh sieve for later use.
[0110] (2) The sample from step (1) was added to 300 mL of a cleaning solution containing surfactants AES and AEO-3. The mass ratio of AES to AEO-3 solution was 1:4 and the concentration was 500 mg / L. The solution was placed in a 40°C water bath constant temperature shaker for 4 hours and 500 W ultrasonic waves (intermittent) were applied to it to ultrasonically clean and remove oil from the waste catalyst powder, resulting in de-oiled waste catalyst powder. In this embodiment, the de-oiling rate of the waste catalyst was 96.95%.
[0111] (3) The spent catalyst powder obtained in step (2) was dried and weighed, with a mass of 8.89 g. 8.89 g of sodium hydroxide granules were weighed according to a mass ratio of spent catalyst to sodium hydroxide of 1:1 and ground in a mortar until fully mixed. The mixture was then transferred to a corundum crucible, placed in a tube furnace, and protected with argon gas to create an oxygen-free environment. After continuous and uniform gas flow for 30 min, the sample was heat-treated at 500℃ for 3 h. 16.95 g of clinker was obtained after the reaction.
[0112] (4) Take the clinker obtained in step (3) and put it into a 250mL beaker. Add 170mL of weakly alkaline aqueous solution. The weakly alkaline solution is prepared with sodium bicarbonate and the pH of the solution is 7.5. Stir magnetically in a 50℃ water bath for 20min. After leaching, centrifuge the sample at high speed. Set the centrifuge speed to 10000rpm / min and the centrifugation time to 10min to obtain a leachate containing Al and Re and a leachate residue containing Pt and a small amount of Re. Dilute the leachate 10 times and 1000 times respectively, and detect the leaching rate of element Re and element Al in the leachate by ICP-OES. The test results show that the leaching rate of Re is 93.50% and the leaching rate of Al is 97.38%.
[0113] (5) Pass the leachate from step (4) into an exchange column containing imprinted resin. The resin is polystyrene imprinted resin. The purchaser and model are the same as in Example 1. The volume ratio of resin to leachate is 1:8. The adsorption temperature is 50℃. The adsorption time is 10 min. The tail liquid of the exchange is sodium aluminate solution. After the adsorption is completed, 128 mL of 1 mol / L sodium hydroxide solution is passed into the resin for desorption according to the volume ratio of desorption liquid to resin is 6:1. The desorption time is 30 min. The desorption temperature is the same as the adsorption temperature to obtain sodium perrhenate solution.
[0114] (6) Add 2 mL of 0.1 mol / L hydrochloric acid solution and 0.8 mL of 18 vol% H2O2 solution to the leaching residue obtained in step (4). In this embodiment, the solid-liquid ratio of leaching residue to hydrochloric acid solution is 1:2 g / mL, and the ratio of leaching residue to hydrogen peroxide solution is 1:0.8 g / mL. The reaction time is 0.5 h and the reaction temperature is 50 °C, and a leachate containing chloroplatinic acid and perrhenic acid is obtained.
[0115] (7) Disperse carbon black in an alkaline ethylene glycol solution, the alkaline solution being sodium hydroxide solution with a pH of 11, and add the leachate obtained in step (6). In this example, the amount of carbon black used is 80 mg, the amount of alkaline ethylene glycol solution is 8 mL, and the volume of leachate is 25 mL. React under microwave assistance, with a microwave power of 800 W, a reaction temperature of 170 °C, and a reaction time of 3 min.
[0116] (8) Add 0.5 mol / L HCl solution to the reaction product obtained in step (7) to adjust the pH to 2 and stabilize it for 36 h. After washing and drying, the modified platinum-based catalyst for regeneration and preparation of fuel cells is obtained.
[0117] The loading of active metals Pt and Re and the electrochemical performance test results of the regenerated catalyst prepared in this embodiment are shown in Table 1. After sample dissolution, ICP-OES analysis showed that the loading of Pt reached 20 wt% and the loading of Re reached 1.12 wt%. The recovered rare and precious metals had a high loading on the carbon black support, meeting the commercial testing conditions. The modified catalyst prepared by regeneration was subjected to electrochemical performance testing (test system and conditions were the same as in Example 1). The half-wave potential of the catalyst prepared in this embodiment was 0.85 V, and its electrochemical performance was superior to that of the commercial Pt / C catalyst (the platinum loading and corresponding half-wave potential of the commercial Pt / C catalyst were the same as in Example 1).
[0118] Example 4: This example uses a method similar to that of Example 1, except that in step (2), 300 mL of a solution containing surfactants AES and APG1214 is added to the sample. The mass ratio of AES to APG1214 is 1:2, and the concentration is 600 mg / L. In this example, the deoiling rate of the waste catalyst is 95.58%. In step (3), 14.61 g of sodium hydroxide particles are weighed according to the mass ratio of waste catalyst to sodium hydroxide of 1:1.6 and ground in a mortar until fully mixed. The heat treatment temperature is 300℃, and the heat treatment time is 5 h. In step (4), 200 mL of a weakly alkaline aqueous solution is added. The weakly alkaline solution is prepared with sodium hydroxide, and the solution pH is 8.5. After leaching, the leachate is diluted 10 times and 1000 times respectively, and the leaching rates of elements Re and Al in the leachate are detected by ICP-OES. The test results show that the leaching rate of Re is 82.13%, and the leaching rate of Al is 92.17%. In step (7), the microwave power is 800W, the reaction temperature is 170℃, and the reaction time is 3min.
[0119] The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this embodiment are shown in Table 1.
[0120] Example 5: This example uses a method similar to that of Example 1, except that in step (2), 600 mL of a cleaning solution containing surfactants SDBS and APG is added to the sample. The mass ratio of SDBS to APG solution is 1:2, and the concentration is 800 mg / L. In this example, the deoiling rate of the waste catalyst is 97.54%. In step (3), 12.53 g of sodium hydroxide particles are weighed according to the mass ratio of waste catalyst to sodium hydroxide of 1:1.4 and ground in a mortar until fully mixed. The heat treatment temperature is 600℃, and the heat treatment time is 2 h. In step (7), the microwave power is 1200 W, the reaction temperature is 180℃, and the reaction time is 2 min.
[0121] The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this embodiment are shown in Table 1.
[0122] Example 6: This example uses a method similar to that of Example 1, except that in step (2), 500 mL of a cleaning solution containing surfactants SLS and AEO-3 is added to the sample. The mass ratio of SLS to AEO-3 solution is 1:2, and the concentration is 900 mg / L. In this example, the deoiling rate of the waste catalyst is 93.87%. In step (3), 9.12 g of sodium hydroxide particles are weighed according to the mass ratio of waste catalyst to sodium hydroxide of 1:1 and ground in a mortar until fully mixed. The heat treatment temperature is 400℃, and the heat treatment time is 3 h. In step (7), the microwave power is 1100 W, and the reaction time is 3 min.
[0123] The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this embodiment are shown in Table 1.
[0124] Example 7: This example uses a method similar to that of Example 1, except that in step (2), 400 mL of a cleaning solution containing surfactants AES and TX-100 is added to the sample. The mass ratio of AES to TX-100 solution is 1:1, and the concentration is 500 mg / L. In this example, the deoiling rate of the waste catalyst is 94.63%. In step (3), 11.0 g of sodium hydroxide particles are weighed according to the mass ratio of waste catalyst to sodium hydroxide of 1:1.2 and ground in a mortar until fully mixed. The heat treatment temperature is 500℃, and the heat treatment time is 1 h. In step (7), the microwave power is 1000 W, the reaction temperature is 190℃, and the reaction time is 2 min.
[0125] The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this embodiment are shown in Table 1.
[0126] Comparative Example 1: The method used in this comparative example is similar to that in Example 1, except that no surfactant is added to the cleaning solution in step (2), and the oil removal rate is 8.6%. Because no surfactant is added, the surface of the spent catalyst contains a large amount of residual oil, which will affect the reaction process in the heat treatment section, reduce the recovery rate of valuable metals, the loading rate of rare and precious metals, and the electrochemical performance of the catalyst. The loading of rare and precious metals and the electrochemical half-wave potential test values in the modified catalyst for regenerated fuel cells prepared in this comparative example are shown in Table 1.
[0127] Comparative Example 2: This comparative example uses a method similar to that of Example 1, except that ultrasound was not applied during the oil removal process of the spent catalyst powder in step (2), and the oil removal rate was 86.58%. Because ultrasound was not added, the removal rate of residual oil on the surface of the spent catalyst was not high, which would affect the reaction process in the heat treatment section, reduce the recovery rate of valuable metals, the loading rate of rare and precious metals, and the electrochemical performance of the catalyst. The loading of rare and precious metals and the electrochemical half-wave potential test values in the modified catalyst for regenerated fuel cells prepared in this comparative example are shown in Table 1.
[0128] Comparative Example 3: This comparative example uses a method similar to that of Example 1, except that only the surfactant SDBS is added to the cleaning solution in step (2), and the oil removal rate is 74.23%. The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerated fuel cells prepared in this comparative example are shown in Table 1.
[0129] Comparative Example 4: This comparative example uses a method similar to that of Example 1, except that only the surfactant AEO is added to the cleaning solution in step (2), and the oil removal rate is 67.52%. The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerated fuel cells prepared in this comparative example are shown in Table 1.
[0130] Comparative Example 5: This comparative example uses a method similar to that of Example 1, except that the sodium thermal treatment in step (3) is not protected by an inert argon atmosphere. Because the rare and precious metal rhenium is exposed to air, the oxidation process produces volatile oxides. The recovery rate of rhenium further decreases, and the rhenium loading in the prepared regenerated catalyst decreases, resulting in a reduction in the catalyst's electrocatalytic activity. The rare and precious metal loading and electrochemical half-wave potential test values in the modified catalyst for regenerated fuel cells prepared in this comparative example are shown in Table 1.
[0131] Comparative Example 6: This comparative example uses a method similar to that of Example 1, except that the oxygen-free sodium treatment temperature in step (3) is 600°C. Increasing the heat treatment temperature is beneficial to the reaction process. The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this comparative example are shown in Table 1.
[0132] Comparative Example 7: This comparative example uses a method similar to that of Example 1, except that hydrogen peroxide, an oxidant, is not added in step (6). Without an oxidant, the rare and precious metals are difficult to dissolve, resulting in a lower loading of the regenerated catalyst and poor electrocatalytic activity. The loading of rare and precious metals and the electrochemical half-wave potential of the modified catalyst for regenerated fuel cells prepared in this comparative example are shown in Table 1.
[0133] Comparative Example 8: This comparative example uses a method similar to that of Example 1, except that the power set for the microwave-assisted process in step (7) is 1100W. Increasing the power of the reaction process results in a more thorough reaction, a more complete reaction of the synthesized catalyst, a larger loading, and better catalytic activity. The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this comparative example are shown in Table 1.
[0134] Comparative Example 9: This comparative example uses a method similar to that of Example 1, except that the microwave-assisted reaction product was not acidified with sulfuric acid in step (8). Maintaining an alkaline environment would affect the coordination of Pt and reduce its electrochemical performance. The rare and precious metal loading and electrochemical half-wave potential test values of the modified catalyst for regenerative fuel cells prepared in this comparative example are shown in Table 1.
[0135] The active metal loading and electrochemical performance of the modified catalysts for fuel cells obtained in the above embodiments were tested, and the test results are as follows:
[0136] Table 1. Active metal loading and electrochemical performance of modified catalysts for fuel cells in examples and comparative examples.
[0137]
[0138]
[0139] As shown in the table above, the modified platinum-based catalyst for fuel cells prepared by this process can achieve a maximum Pt loading of 22.3 wt% and a maximum Re loading of 1.35 wt%, which meets the requirements for normal device operation. Electrochemical testing revealed an optimal half-wave potential of 0.87 V, demonstrating excellent electrochemical performance.
[0140] The above description only illustrates several specific embodiments of the present invention, but it should not be construed as the scope of protection of the present invention. Any equivalent changes or modifications, or proportional enlargements or reductions made in accordance with the design spirit of the present invention should be considered to fall within the scope of protection of the present invention.
Claims
1. A method for regenerating platinum-rhenium spent catalyst to prepare modified platinum-based catalysts for fuel cells, characterized in that, Includes the following steps: (1) Removing oil from platinum-rhenium waste catalyst with alumina as support: Grind the platinum-rhenium waste catalyst into powder, add a compound surfactant solution and clean it under ultrasonic conditions to obtain de-oiled waste catalyst; The compound surfactant is composed of a nonionic surfactant and anionic surfactant. (2) The waste catalyst treated in step (1) and sodium hydroxide powder are mixed and then heat-treated in an oxygen-free environment to obtain clinker; (3) The clinker is leached in a weakly alkaline aqueous solution to obtain a first leachate containing Al and most of Re and a first leach residue containing Pt and a small amount of Re; (4) The first leachate is converted into sodium aluminate solution and sodium perrhenate solution. Specifically, the first leachate is passed into an exchange column containing an imprinted resin that can selectively adsorb rhenium anion groups, and the exchange tail liquid is collected to obtain the sodium aluminate solution. After the adsorption is completed, the desorption liquid is passed into the resin for desorption to obtain the sodium perrhenate solution. (5) Add an aqueous solution of an acidic reagent and an aqueous solution of an oxidizing reagent to the first leaching residue for oxidative acid leaching to obtain a second leaching solution containing precursors of platinum and rhenium. The oxidizing agent is hydrogen peroxide; (6) The precursor containing platinum and rhenium in the second leachate is reduced and loaded onto a carbon support to obtain a rhenium-doped Pt / C catalyst, thereby obtaining the modified platinum-based catalyst for fuel cells.
2. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to claim 1, characterized in that: The mass percentage of alumina in the platinum-rhenium-containing waste catalyst is 95-97%. The platinum-containing rhenium waste catalyst has a platinum content of 0.2% to 0.3% by mass. The mass percentage of rhenium, the active metal component, in the platinum-rhenium-containing waste catalyst is 0.4-0.5%. The powdered form is a platinum-rhenium spent catalyst with a particle size of 100-200 mesh. The nonionic surfactant is selected from any one of fatty alcohol polyoxyethylene ether, Triton X-100 and glucoside; The anionic surfactant is selected from any one of sodium dodecylbenzene sulfonate, sodium fatty alcohol polyoxyethylene ether sulfate, and sodium dodecyl sulfonate. The mass ratio of the nonionic surfactant to the anionic surfactant is (1~4):1; The concentration of the compound surfactant solution is 100~1000 mg / L; The mass ratio of the platinum-rhenium-containing waste catalyst to the volume ratio of the aqueous solution of the surfactant is 1 g : (10~100) mL; The ultrasonic power is 100~500W, the cleaning temperature is 25~60℃, and the cleaning time is 1~4h.
3. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to claim 1, characterized in that: In step (2), the mass ratio of the waste catalyst treated in step (1) to the sodium hydroxide powder is 1:(0.8~1.6). The oxygen-free environment is under the protection of an inert gas; The heat treatment is performed at a temperature of 300~600℃ for 1~5 hours.
4. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to claim 1 or 2, characterized in that: In step (3), the pH value of the weakly alkaline aqueous solution is 7.1~8.9; The solute in the weakly alkaline aqueous solution is sodium hydroxide, sodium carbonate, or sodium bicarbonate. The mass ratio of the clinker to the volume ratio of the weakly alkaline aqueous solution is 1g:(10~20)mL; The leaching is carried out under stirring conditions, with a leaching temperature of 25~60℃ and a leaching time of 10~60min.
5. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to any one of claims 1-3, characterized in that: The imprinting resin is an ion-imprinted imprinting resin containing polystyrene groups. The volume ratio of the first leachate to the imprinted resin is (5~10):1, the adsorption temperature is 25~50℃, and the adsorption time is 10~30min; The desorption solution is a sodium hydroxide solution with a concentration of 1~2 mol / L. The volume ratio of the desorption solution to the imprinted resin is (5~10):
1. The desorption temperature is 25~50℃ and the desorption time is 30~120 min.
6. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to any one of claims 1-3, characterized in that: In step (5), the acidic reagent is hydrochloric acid; The concentration of the aqueous solution of the acidic reagent is 0.1~0.5 mol / L; The mass ratio of the first leaching residue to the volume ratio of the aqueous solution of the acidic reagent is 1 g : (1~5) mL; The volume concentration of the aqueous solution of the oxidizing agent is 10-30%; The mass ratio of the first leaching residue to the volume ratio of the aqueous solution of the oxidizing agent is 1 g : (0.5~1) mL; The oxidative acid leaching temperature is 25~50℃, and the time is 0.5~2h; The precursors containing platinum and rhenium are chloroplatinic acid and perrhenic acid.
7. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to any one of claims 1-3, characterized in that: In step (6), the process of reducing the precursor containing platinum and rhenium in the second leachate and loading it onto the carbon support is as follows: the carbon support is dispersed in an alkaline ethylene glycol solution, the second leachate is added, a reduction reaction is carried out under microwave assistance, and the reaction product is acidified, washed and dried in sequence to obtain the modified platinum-based catalyst for fuel cells. The carbon support is carbon black, graphene, or carbon nanotubes. The alkaline ethylene glycol solution has a pH of 11-12, and the alkaline reagent is sodium hydroxide solution; The volume ratio of the alkaline ethylene glycol solution to the second leachate is (2~11):25; The microwave power is 800~1200W, and the operation is carried out under normal pressure conditions; The reduction reaction is carried out at a temperature of 140~190℃ for 2~3 minutes. The pH value is adjusted to 2-3 during the acidification step; The acidification step uses dilute hydrochloric acid, dilute sulfuric acid, or dilute nitric acid. The stabilization time in the acidification step is 12~36h.
8. The method for preparing modified platinum-based catalysts for fuel cells by regenerating platinum-rhenium spent catalysts according to any one of claims 1-3, characterized in that: The modified platinum-based catalyst for fuel cells has a Pt loading of 5-30% and a Re loading of 0.5-1.5%.
Citation Information
Patent Citations
Method for removing landification dead catalyst oiliness material
CN101380597B
Method for selectively dissolving and recovering platinum from platinum-containing waste catalysts
CN107190147A
A method for extracting rhenium from a depleted platinum-rhenium catalyst
CN108913919B
Method for preparing Pt / C catalyst from platinum-containing waste catalyst
CN109126777A
Method for removing oil on surface of waste oil refining catalyst
CN114522699A